Retail Diversity for Diet Diversity - Dietary Intake Data - Raneri, Jessica Evelyn; Hoang The Ky; Wertheim-Heck, Sigrid C.O. (Bioversity International, 2020)
Households were randomly selected from the field sites, where women were asked to recall all the foods and drinks they consumed the previous day, and specifying where those foods were sourced from. An adapted quantiative 24hour recall methodology was applied